Shall We Play the Same? Pedagogical Perspectives on Infants’ and Children’s Imitation of Musical Gestures - Filippa, Manuela; Monaci, Maria Grazia; Young, Susan; Grandjean, Didier; Nuti, Gianni; Nadel, Jacqueline (Frontiers in Psychology, 2020)
Imitation, both gestural and vocal, has been acknowledged to be at the origin of human communication (Donald, 1991). Music is often considered to be the first means of communication of emotion via both vocal and gestural synchronization (Malloch, 1999; Malloch & Trevarthen, 2009). Instrumental music is part of the human heritage for more than 35000 years before our era (Aimé, Le Covec, Bovet & Esseily, 2020). However, very little is known about the acquisition of gestures that produce sounds (i.e. musical gestures) and their role in the development of music and musicality. In the present paper, we propose that studying early synchronous imitation of musical gestures is essential both for investigating the development of the early action–perception system and for outlining early music interventions during infancy. We designed double musical objects which can be used in preschool music education for prompting synchronic imitation of musical gestures between adult and child, and between dyads of infants. We conclude by proposing a novel pedagogical perspective in music education for the early years which links the privileged orientation of infants and children towards sound discoveries with the development of perception-action coupling via imitation of musical gestures.